Effects of sugarcane-derived polyphenol supplementation on ruminal fermentation, methane emission, and microbiome in Holstein cows - Marino, Elizangela Domenis; de Toledo, Ariany Faria; Virgínio Júnior, Gercino Ferreira; Mendes, Lucas William; Soares, Weber Vilas Bôas; Roma Júnior, Luiz Carlos; Bittar, Carla Maris Machado (Frontiers in Animal Science, 2026)
The use of plant-derived polyphenols in ruminant nutrition has garnered attention as a natural approach to enhance fermentation efficiency, mitigate methane emissions, and improve animal health. This study evaluated the effects of sugarcane‐derived polyphenol supplementation on ruminal fermentation, methane emission, blood parameters, and the ruminal microbiome of lactating Holstein cows. Sixteen cows were assigned to two treatments: Control (50 mL/d placebo) or Polyphenol (50 mL/d sugarcane polyphenol extract). Ruminal fluid was analyzed for short-chain fatty acids (SCFAs) and ammonia-N, blood was analyzed for selected metabolites, methane emissions were measured using the SF6 technique, and microbial diversity and composition were assessed by 16S rRNA gene sequencing. Polyphenol supplementation increased total SCFA concentration from 58.44 to 66.44 ± 3.00 mM (P = 0.08) and raised the molar proportion of propionate from 18.13 to 18.89 ± 0.29 mM/100 mM (P = 0.08). Blood glucose concentrations were significantly higher in supplemented cows, whereas other blood parameters were unaffected. Methane emissions did not differ between groups. Microbial community analyses revealed no effect on alpha diversity measures (Shannon index and richness), but an impact of treatment and time in beta diversity, with polyphenol supplementation associated with selective shifts in bacterial taxa, including greater relative abundance of Planctomycetota. These findings indicate that sugarcane‐derived polyphenols can beneficially modulate ruminal fermentation and microbial community structure without compromising microbial diversity. The increase in propionate and blood glucose suggests enhanced glucogenic potential, while unchanged methane emissions highlight the need for further studies to clarify the conditions under which sugarcane polyphenols may mitigate greenhouse gas emissions.